Fuzzy based Manu's fire segmentation algorithm. (3rd November 2020) - Chhetri, Pratik; Banu, P.K. Nizar
Forests are the primary source of natural resources and oxygen of the planet, thus any harm to the forest imbalances the natural environment. One of the primary reason for this imbalance are forest fires which requires a rigid fire surveillance system to detect fire effectively. The objective of this paper is to build a better algorithm for fire region segmentation regardless of different light illumination conditions. The algorithm uses CIE L*a*b* color space which plays a crucial role to scrutinise each fire pixel of the image and a set of fuzzy value range from 0.1 to 0.9 is used to increase the rate of accuracy of segmentation. The proposed algorithm is presented in two parts, images with extra background light source and images with low background light source which makes the segmentation process robust. A synthetic dataset created and tested with the algorithm and the results are much satisfying.